Fatwa and the internet: a study of the influence of Muslim religious scholars on internet diffusion in Saudi Arabia. (1st June 2014) - Al-Kandari, Ali A.; Dashti, Ali
Abstract : This study uses diffusion of innovations theory to examine the influence of Muslim religious scholars on internet diffusion in Saudi Arabia. It applies content analysis to the fatwa, the religious edicts that Muslim religious scholars issue, to explore fatwa decisions relating to the internet since its launch in Saudi Arabia in 1999. There are 34 fatwa in total, 11 with approving decisions, 11 with disapproving ones, and 12 with conditionally approving decisions. Those who issue approving fatwa argue that it helps to spread the word of Allah and that if Muslims do not exploit the opportunities provided by the internet, then non-Muslims and non-believers will use it for evil. To explain their disapproving fatwa, other scholars argue that the internet corrupts people. The study discusses the impact of religion and religious scholars on the dissemination of communication technologies in Saudi society. It also predicts a pattern of opinions that scholars may be expected to adopt on the introduction of any new communication technology that is culturally controversial.